The Relationship Between Rainy Day and Sunshine Duration with Dengue Hemorrhagic Fever Incidence in City of Yogyakarta - Aunillah , Alvian; Kesetyaningsih , Tri (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction – Dengue fever is a disease that often occurs in tropical countries, including Indonesia. DHF is caused by the dengue virus from the Flaviviridae family and infects through the Aedes aegypti or Aedes albopictus mosquitoes. DHF transmission is related to the survival capacity, behavior, and habitat of mosquito as vectors, therefore it may be influenced by climatic factors such as the number of rainy days and the sunshine duration. Purpose – The aim of the study was to determine whether the number of rainy days and the sunshine duration were correlated with the incidence of dengue fever in the city of Yogyakarta. Methodology/Approach – This study uses a retrospective analytic observational method. This study was conducted by analyzing the relationship between monthly data on the number of rainy days and duration of sunshine with cases of dengue fever in the city of Yogyakarta in 2015-2019. Climatic data were obtained from the recording of the Yogyakarta Mlati Climatology Station and data on dengue cases were obtained from the records of the Yogyakarta City Health Office. The data was then analyzed by the Spearman correlation test to find the correlation between the two variables. DHF with an accumulation of 3705 cases during 2015-2019. The city has a tropical climate with an average of 8.96 rainy days and 66% of sunshine duration per month. In the Spearman correlation test, it is found that there was no relationship between DHF cases and the number of rainy days, which had a non-significant positive correlation (p = 0.056 ; r = 0.249) and there was no relationship between DHF cases and sunshine duration had a negative and insignificant correlation (p = 0.316; r = - 0.132). There is no significant relationship between the number of rainy days and the sunshine duration with the incidence of DHF in the city of Yogyakarta. There is a difference in the direction of the correlation between the two variables, namely the number of rainy days is positively correlated while the sunshine duration is negatively correlated with the incidence of DHF in Yogyakarta City. Originality/ Value/ Implication – This study proves that the factor of the number of rainy days shows a positive correlation with the number of cases of DHF, while the factor of the sunshine duration shows a negative correlation in the city of Yogyakarta.